Analisis Penerapan Fungsi Manajemen Imarah Dalam Pengelolaan Pendidikan Islam Nonformal - Muhammad Royyan Abrar; Khairul Habibi; Kamaruddin (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2026)
This study examines the management functions of Baiturrahman Mosque in Lhokseumawe City through four dimensions: planning, organizing, implementation, and supervision. Using a qualitative approach, data were collected from interviews with core administrators, imam rawatib, marbot, worshippers, and the Head of Facilities and Infrastructure. The findings show that program planning for religious, social, and facility maintenance activities is conducted through routine deliberation, although documentation remains simple and not yet digitalized. Organizing is supported by a functional structure and clear task division, but inter-field coordination and financial transparency require improvement. Program implementation is generally effective due to collective leadership and congregational support, yet youth participation and social program development remain limited. Supervision is carried out through daily monitoring, evaluation meetings, and worshipper feedback. The study recommends preparing SOPs, digitalizing administration and finance, strengthening communication systems, and developing performance-based evaluation mechanisms to promote professional and accountable mosque management.